Bacteraemia Following Different Orthodontic Treatment Procedure - Al-Khatieeb, Mustafa M. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: since the occurrence of transient bacteraemia is fatal following different dental procedures in patients at-risk of bacterial endocarditis, the purpose of this research was to estimate the percentage and nature of bacteraemia following four orthodontic treatment procedures which were: an upper alginate impression, separator placement, band fitting or placement, and arch wire adjustment on a fixed appliance.Materials and methods: the study group consisted of 40 patients (25 females and 15 males) ranging from 17-25 years of age attending Orthodontic Department in the College of Dentistry/Baghdad University, and out patients department from private clinic. The 40 patients were divided into four groups (10 patients each). A cannula was inserted into either the left or right antecubital fossa using an aseptic technique. A 5ml of blood was taken immediately before orthodontic treatment procedure and a second 5ml sample was taken 1-2 minutes after the procedure.Results: the blood samples showed a percentage of bacteraemia of 50%, 40%, 30%, and 20% in cases of post-band placement, post-separator placement, post-arch wire adjustment, and post-alginate impression procedures respectively.Conclusion: this investigation demonstrated that the placement of separator and fitting of band procedures could cause a significant bacteraemia, thus these procedures for patients at–risk of bacterial endocarditis should be placed in consideration, and prescribe the necessarily antibiotic coverage.